Effect of ROA, CAR, NPF, and BOPO on Mudharabah Financing (Empirical Study of Indonesian Sharia Commercial Banks in 2018-2020) - Adhi Widyakto; Aprih Santoso; Risti Ulfi Hanifah; M. Sigit Taruna (Jurnal Maksipreneur, 2023)
The purpose of this study is to empirically examine the effect of return on assets, capital adequacy ratio, non-performing finance, and BOPO ratio on the Mudharabah Financing System. The samples in this study are eight Sharia Banks in Indonesia registered with the Financial Services Authority (OJK) RI in 2018-2020, which were obtained through a purposive sampling technique approach. The data analysis method uses multiple linear regressions. This is indicated by the results of research using the t-test ROA and BOPO have no effect on the Mudharabah Financing system, while CAR and NPF had a significant positive effect on mudharabah's approval of Sharia Banks. Sharia Banks in managing to finance must prioritize the principle of prudence so that bad debts can be controlled.